Erosi Kualitatif Pada Perkebunan Karet Umur 25 Tahun di Desa Lau Damak Kecamatan Bahorok, Kabupaten Langkat - M Hadi Syahlan Hasibuan; Abdul Rauf; Bintang Sitorus (Jurnal Agroekoteknologi, 2015)
This research was aims to study the qualitative erosion on land cultivation of 25 Years old rubber trees in Lau Damak Village, Bahorok District, Langkat Region. The research was conducted from September-December 2014 by doing field activities and laboratory activities. Field activities was sampling the soil on slope 26-28 % with textured sandy clay loam, then the soil samples were analysed at BPTP Laboratory, Medan. Then the results of the analysis were processed by T-test.The results showed P-available,CEC and clay fraction is significant on slope position, but not significant to N-total, K-dd and C-organic. The highest average of CEC and clay fraction are in the middle of the slope. The highest average N-total and C-organic are in the slope above. The highest average pH, P-available and K-dd are in the lower slopes, the bulk density in each slope have a same value.Key words : Qualitative erosion, , 25 years old rubber trees